Working at the interface: call-centre labour in a global economy. (1st July 2009) - Ursula Huws,
Abstract : Introducing this volume, this paper describes the contradictory nature of many aspects of call-centre work, drawing on the results of the EC-funded STILE project to demonstrate the difficulties of classifying call-centre workers. The lack of a clear objective 'place' in the technical division of labour and the social order for this transient and poorly-defined workforce is mirrored by a subjective failure, on the part of call-centre workers, to identify themselves as such. This makes it difficult to develop stable collective occupational identities that could form a basis for organisation and representation. Such conflicts are exacerbated by call-centre workers' position 'at the interface' between companies and their customers and between the local and the global. Many are also having to deal with the difficult transition from other types of work to call-centre work as the process of 'callcenterisation' sweeps through the public sector as well as private companies. The paper concludes by noting that, despite many similarities between call centres across the globe, national industrial relations systems and other aspects of particular locations still make a significant difference to the working conditions of call-centre workers.